PKM Pelatihan dan Praktek Proses Instalasi Jaringan CCTV Kepada PKL - Atmaja, R Ferry Bakti; Dendi R, Agus; Amir A, Ari; Isnanto, Burham; Supardi, Supardi (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The rapid development of Closed Circuit Television (CCTV) technology has increased the need for skilled personnel in the installation and maintenance of surveillance systems. However, the gap between industry needs and the competence of SMK graduates is still a challenge, mainly due to limited practical facilities and a less adaptive curriculum. Therefore, a CCTV network installation training programme for SMK students is needed. The programme of activities was designed to address these challenges through a theoretical and practical approach. The 3-day training covers the introduction of CCTV technology, system design, physical installation, network configuration, and troubleshooting, using campus facilities as a practical laboratory. Multimedia learning methods in the form of visual and video presentations were applied to strengthen theoretical understanding, while field practice involved installation in the campus environment. The resulting outputs include an increase in the technical competence of participants as reflected in the ability to self-install and certify, the realisation of a functional CCTV system on campus, as well as long-term impacts such as increasing the competitiveness of graduates and educating the public about digital security. Evaluation of success was conducted through competency tests, project feasibility, and questionnaires. This kind of programme not only tries to fill the skills gap in the vocational field but also fulfils the urgency of the digital era.ABSTRAKPerkembangan teknologi Closed Circuit Television (CCTV) yang pesat telah meningkatkan kebutuhan akan tenaga terampil di bidang instalasi dan pemeliharaan sistem pengawasan. Namun, kesenjangan antara kebutuhan industri dan kompetensi lulusan SMK masih menjadi tantangan, terutama akibat keterbatasan fasilitas praktik dan kurikulum yang kurang adaptif. Oleh karena itu diperlukan sebuah program pelatihan instalasi jaringan CCTV bagi siswa SMK. Program kegiatan dirancang untuk menjawab tantangan tersebut melalui pendekatan teori dan praktik. Pelatihan selama 3 hari mencakup pengenalan teknologi CCTV, desain sistem, pemasangan fisik, konfigurasi jaringan, hingga troubleshooting, dengan menggunakan fasilitas kampus sebagai laboratorium praktik. Metode pembelajaran multimedia berupa presentasi visual dan video diterapkan untuk memperkuat pemahaman teoritis, sementara praktik lapangan melibatkan instalasi di lingkungan kampus. Keluaran yang dihasilkan meliputi peningkatan kompetensi teknis peserta yang tercermin dari kemampuan instalasi mandiri dan sertifikasi, terwujudnya sistem CCTV fungsional di kampus, serta dampak jangka panjang seperti peningkatan daya saing lulusan dan edukasi masyarakat tentang keamanan digital. Evaluasi keberhasilan dilakukan melalui uji kompetensi, kelayakan proyek, dan kuesioner. Program semacam ini tidak hanya mencoba mengisi kesenjangan keterampilan pada bidang vokasi tetapi juga memenuhi urgensi pada era digital.